2003
DOI: 10.1167/iovs.02-0499
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Ciprofloxacin Levels after Oral Administration in Silicone Oil-Filled Eyes

Abstract: Antibiotic levels in the RSOF in SO-filled eyes after oral administration of ciprofloxacin in two 750-mg doses exceeded the minimal inhibitory concentration for 90% of isolates (MIC(90)) for most bacterial species and was higher than levels reached in the vitreous in nonvitrectomized eyes (P = 0.001).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…However, 50% of group 2 patients (3/6) had a useful final visual outcome (Fisher's exact test: upper tail P=0. 16, lower tail P=0.03). Thus, while poor outcomes were noted in both the groups, useful visual outcomes were seen following surgery only in group 2 patients.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, 50% of group 2 patients (3/6) had a useful final visual outcome (Fisher's exact test: upper tail P=0. 16, lower tail P=0.03). Thus, while poor outcomes were noted in both the groups, useful visual outcomes were seen following surgery only in group 2 patients.…”
Section: Discussionmentioning
confidence: 92%
“…The attenuated vitreous phase lying adjacent to the inflamed retinal surface, which forms the posterior compartment, is also likely to achieve high antibiotic levels following intravenous administration due to the absence of diffusion into the vitreous cavity. Support for this hypothesis has come in a study carried out by us in which it was shown that antibiotic levels in the retro-silicone oil space after oral administration of ciprofloxacin in two 750-mg doses exceeds the MIC 90 for most bacterial species [16].…”
Section: Discussionmentioning
confidence: 97%
“…Moxifloxacin concentrations were determined in each of the samples using a previously described highperformance liquid chromatography technique (HPLC) used for estimation of intraocular ciprofloxacin with slight modifications. 17 Briefly, Thermo Surveyor HPLC (Thermo Electron Corporation, USA) connected with an autosampler, online degasser and photodiode array detector (model 996;Waters) was used. Acetonitrile and phosphate buffer (20 mM) with pH 2.5 (adjusted with phosphoric acid) was used at the ratio of 25 : 75 pumped at the rate of 1 ml/min.…”
Section: Methodsmentioning
confidence: 99%
“…The processing was as per our previous publication. 4 (6) Kampougeris et al also mention that the results of our paper have to be interpreted with caution. We too have not claimed so and have mentioned the need for future studies in our paper.…”
mentioning
confidence: 68%